Recommendation for Standardization of Botanical Nomenclature in Traditional and Complementary Medicinal Systems - Vinay M. Raole; Vaidehi V. Raole (Journal of Tropical Ethnobiology, 2022)
Plant Nomenclature is an essential requirement for publications in drug discovery and in pharmacological investigations in modern and traditional medical systems. Mostly names of plants can be presented by pharmaceutical names or scientific binomial names. In this paper, good and bad aspects of both systems are discussed in the context of the recent scientific nomenclatural framework and the systems for its practical applicability. WHO Programme for International Drug Monitoring and is responsible for the WHO Adverse Drug Reaction (ADR) database that currently contains 3.6 million records. Numerous plant species are used in various formulations of TCM but we are not sure which particular plant species is used as a whole plant or plant part is used for example Aloe and Piper. In order to monitor pharmacovigilance to herbal medicine products the following nomenclatural criteria are important: (i) only one species of plant name should indicate; (ii) author citation is essential; (iii) it should indicate which of plant part is used. Scientific botanical nomenclature as defined by the International Code of Botanical Nomenclature will a better option. We are of the belief that the adoption of scientific names of plants to denote plant ingredients in traditional formulations are strongly endorsed. This decision if adopted will satisfies all criteria set up by upgrading an old inconsistent system used in publications and formulations will become obsolete.